Strategic positioning in the oil industry trends and options - Stevens, Paul 1947- (Emirates Center for Strategic Studies and Research, 2014)
An increase in the overall world oil supply and an intensification of competition in the industry has forced oil producers to search for new technologies in order to remain competitive in the world market. Strategic positioning, the subject of this study, plays an important role